PENGEMBANGAN APLIKASI SMARTSCHOOL BERBASIS WEB UNTUK ADMINISTRASI SEKOLAH DASAR DENGAN AGILE SCRUM - Ramdhani, Rizky Budi; Zakir, Ahmad (PROGRESS, 2025)
The development of information technology has encouraged many educational institutions to adopt digital systems in order to improve the efficiency and accuracy of school administration management. However, at SD Qurratu A’yun, administrative processes such as recording student data, teacher data, and financial transactions are still carried out manually, leading to various problems such as data loss, reporting delays, and inconsistent information. Based on a case study at SD Qurratu A’yun, a web-based school administration information system was developed as a digital solution. The system was designed using the Agile method with a Scrum approach, enabling iterative development that is responsive to user needs. The development process involved several stages: product backlog planning, Sprint planning, Sprint backlog development, daily Scrum meetings, Sprint review, and Sprint retrospective. The system is equipped with key features such as teacher, student, and class data management, transaction type management, cash transactions, and financial reports accessible by academic year. System testing showed that the developed solution successfully improved data organization, accelerated reporting processes, and provided ease of access to information in real time for administrators, treasurers, and principals. By applying the Agile (Scrum) method and building a web-based system, this research provides an optimal solution to the challenges of manual administration at SD Qurratu A’yun. The system not only streamlines workflows but also supports the sustainability of school operations in a more efficient and structured manner.